I didn't come here to leave [compact disc] - Young, Chris, 1985-; Young, Chris, 1985- (Black River Entertainment, 2025)
Chris Young kicks off a bold new era in his career with his 10th studio album, which includes the title track as well as the single Til the Last One Dies.